Intrinsic Axonal Growth and the Drive for Regeneration - O'Donovan, Kevin J. (Frontiers in Neuroscience, 2016)
Following damage to the adult nervous system in conditions like stroke, spinal cord injury or traumatic brain injury, many neurons die and most of the remaining spared neurons fail to regenerate. Injured neurons fail to regrow both because of the inhibitory milieu in which they reside as well as a loss of the intrinsic growth capacity of the neurons. If we are to develop effective therapeutic interventions that promote functional recovery for the devastating injuries described above, we must not only better understand the molecular mechanisms of developmental axonal growth in hopes of re-activating these pathways in the adult, but at the same time be aware that re-activation of adult axonal growth may proceed via distinct mechanisms. With this knowledge in hand, promoting adult regeneration of central nervous system neurons can become a more tractable and realistic therapeutic endeavor.